The Effect of Using the Strategy of Employee Participation in Decision-making In Change Programs on Job Satisfaction among the Employees of The Ministry of Municipal, Rural Affairs and Housing in Riyadh - Almawkili, Abdulaziz (The Arab Journal of Administration, 2023)
This study aimed to discover the effect of using the strategy of employee participation in decision-making in change programs on job satisfaction among the employees of the Ministry of Municipal, Rural Affairs and Housing in the Kingdom of Saudi Arabia. The study was applied to a random sample of employees amounting to (288) employees from the Riyadh region, and the questionnaire was used as a tool for the study consisting of three axes: The first axis: the level of participation of employees in change programs in decision-making and job satisfaction. The second axis: the field of participation of workers in change programs in decision-making and job satisfaction. The third axis: methods and mechanisms for the participation of workers in change programs in decision-making and job satisfaction. The study reached several results, the most important of which is that the general average of the impact of the employees’ participation in decision-making on job satisfaction is high. The study also reached several proposals, the most important of which is strengthening the role of employees and urging them to participate in decision-making in change programs along with the heads.